Hubungan Keseimbangan Kehidupan Kerja dengan Stres Akademik Mahasiswa Pekerja di Universitas PGRI Palembang - Dera Puspita Sari; Nurlela Nurlela; Endang Surtiyoni (Jurnal Pustaka Cendekia Pendidikan, 2026)
This study aims to determine the relationship between work-life balance and academic stress among working students at Universitas PGRI Palembang. Students who take on dual roles as both learners and workers often face various demands that can affect their work-life balance and trigger academic stress. This study employed a quantitative approach with a correlational design. The research population consisted of all 87 students from the Faculty of Engineering at Universitas PGRI Palembang, class of 2023, with a sample of 25 working students selected through purposive sampling. Data were collected using a closed-ended questionnaire with a Likert scale and analyzed using the Product Moment correlation technique. The results show that there is a [negative/positive] and significant relationship between work-life balance and academic stress among working students. This is evidenced by a correlation coefficient of [insert r-value, e.g., -0.654] with a significance value of [insert p-value, e.g., 0.000], which is less than 0.05. These findings indicate that the higher the level of work-life balance maintained by working students, the lower their level of academic stress. Conversely, lower levels of work-life balance are associated with higher levels of academic stress. The results of this study are expected to serve as a valuable reference for students, the university, and future researchers in efforts to understand and manage academic stress among working students.